LATEST PERSPECTIVES IN BACTERIAL BIOFILM ERADICATION (Journal of Medical & Health Sciences Review, 2025)
Biofilms are complex communities of microorganisms encased in extracellular polymeric substances (EPS) that develop on various surfaces in different environments. They show a remarkable ability to resist antimicrobials, presenting significant challenges in healthcare, industry, and environmental management. This review investigates the various stages of biofilm formation, from the initial attachment phase to maturation, and compares single-species biofilms with multispecies ones, highlighting their structural intricacies and functional behaviors. Key environmental factors, such as surface characteristics and nutrient availability, are critical to the development of biofilms. While they can provide advantages like increased resistance and resource acquisition, biofilms are also responsible for ongoing infections and biofouling issues. Moreover, emerging strategies for managing biofilms, including phage therapy and innovative delivery systems, are examined. The review underscores the necessity for ongoing research to enhance biofilm management, especially in tackling antimicrobial resistance and formulating effective treatment options.